Unveiling unusual coloration in amorphous phosphate pigments: a study inspired by the mineral Brazilianite - Onoda, Hiroaki; Higuchi, Kanata; Charoonsuk, Thitirat; Pulphol, Phieraya; Muanglhua, Rangson; Vittayakorn, Naratip (My University, 2026)
Brazilianite, with the formula NaAl3(PO4)2(OH)4, exhibits an intriguing pale yellow to green coloration, a phenomenon not readily explained by the absence of conventional d-block chromophoric metal ions. This study investigates the synthesis of amorphous phosphate-based pigments compositionally analogous to Brazilianite, aiming to replicate and understand the origin of its distinctive coloration through controlled precursor stoichiometry and thermal processing. Sodium, aluminum, and phosphate precursors were precisely mixed and thermally treated. X-ray diffraction (XRD) confirmed the predominantly amorphous nature of the synthesized materials, irrespective of achieving long-range crystalline order analogous to mineral Brazilianite. Despite this, samples processed at intermediate temperatures (e.g., 300–400 °C) exhibited a consistent yellowish hue. This non-conventional coloration, attributed to intrinsic electronic or structural features within the amorphous phosphate network rather than traditional chromophores, represents a significant scientific innovation. This coloration was found to be intrinsically linked to the phosphate network itself. Stability assessments in acidic (0.1 wt% H2SO4) and basic (0.1 wt% NaOH) environments revealed significant vulnerability, attributed to the facile dissolution of sodium and aluminum phosphate species. Notably, the yellowish coloration persisted across various Na/Al/P compositional ratios, even with systematic variations in aluminum or sodium content. This strongly suggests that the observed color is not critically dependent on a precise Na: Al stoichiometry but is fundamentally governed by the local electronic structure within the phosphate network, potentially involving defect centers or specific P-O-Al/Na linkages. These findings offer valuable insights into designing novel, non-toxic, color-stable pigments where coloration arises from mechanisms beyond traditional transition metal ion incorporation, highlighting the potential role of controlled disorder in phosphate-based materials for sustainable applications.
Keywords: Amorphous materials; Brazilianite analogue; Defect-induced color; Inorganic phosphate pigments; Materials inspired by nature; Non-chromophoric color; Phosphate network; Unusual coloration